دلالات الحذف في القرآن الكريم - عطار، فؤاد شيخ الدين (جامعة البحر الأحمر, 2012)
يتناول هذا البحث دلالات الحذف في القرآن الكريم ويقع في مقدمة وأربعة مباحث على ما يلي: \ المبحث الأول: عن الحروف المحذوفة. \ المبحث الثاني: عن حذف الكلمات المفردة. \ المبحث الثالث: عن أشباه الجمل. \ المبحث الرابع: عن الجمل. \ تشتمل الخاتمة على أهم نتائج البحث. This study tackles the meaning of (Hathf) omission in the Holy Quran. It comprises an introduction and four chapters as follows: \ The first chapter deals with the case omitted letters which is the least type of omission that hardly affect the meaning. \ The second chapter discusses omission of single words. It is the most occurring case and has great affect on the meaning. \ The third chapter explains omission of phrases; it occurs in few Cases and has little affected on the meaning. \ The fourth chapter examines omission of full sentences which also has great affect on the meaning.
Keywords: اللغة العربية -- الحذف -- القرآن الكريم -- بلاغة القرآن